Cortical Laminar Necrosis Caused by Immunosuppressive Therapy and Chemotherapy - Bargalló, Nuria; Burrel, Marta; Berenguer, Joan; Cofan, Federico; Buñesch, Laura; Mercader, Josep M. (American Journal of Neuroradiology, 2000)
Summary: We report three patients in whom neurologic symptoms and cortical laminar necrosis developed after immunosuppressive treatment (cyclosporin A and FK 506) and polychemotherapy (vincristine and methotrexate). Initial neuroradiologic studies showed cortical and white matter involvement. Follow-up studies showed cortical hyperintense lesions on T1-weighted MR images, consistent with cortical laminar necrosis. The clinical and radiologic data indicate that a transient hypoxic-ischemic process could have been responsible for the encephalic lesions in these three patients.